2005
DOI: 10.1093/molbev/msi082
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of the Active MITE Transposons mPing and Pong in Rice by Introgression from Wild Rice (Zizania latifolia Griseb.)

Abstract: Hybridization between different species plays an important role in plant genome evolution, as well as is a widely used approach for crop improvement. McClintock has predicted that plant wide hybridization constitutes a "genomic shock" whereby cryptic transposable elements may be activated. However, direct experimental evidence showing a causal relationship between plant wide hybridization and transposon mobilization has not yet been reported. The miniature-Ping (mPing) is a recently isolated active miniature i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
162
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(177 citation statements)
references
References 76 publications
11
162
2
2
Order By: Relevance
“…Another example of transposable element (TE) mobilization comes from intergeneric hybridization between rice (cultivar Matsumae) and wild rice (Zizania latifolia). Shan et al (2005) used a repeated pollination procedure to generate a series of morphologically distinct inbred lines of rice with introgressed genomic DNA from wild rice, and showed that mPing miniature inverted-repeat transposable element (MITE) and its transposase-encoding partner, Pong, were mobilized in these lines. In contrast, these two MITEs remained immobile in control lines sharing the same parentage to the experimental lines but possessing no introgressed DNA.…”
Section: Transposable Element Derepression During Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of transposable element (TE) mobilization comes from intergeneric hybridization between rice (cultivar Matsumae) and wild rice (Zizania latifolia). Shan et al (2005) used a repeated pollination procedure to generate a series of morphologically distinct inbred lines of rice with introgressed genomic DNA from wild rice, and showed that mPing miniature inverted-repeat transposable element (MITE) and its transposase-encoding partner, Pong, were mobilized in these lines. In contrast, these two MITEs remained immobile in control lines sharing the same parentage to the experimental lines but possessing no introgressed DNA.…”
Section: Transposable Element Derepression During Hybridizationmentioning
confidence: 99%
“…Dobzhansky-Muller's model of genetic incompatibilities has long provided a useful theoretical framework for speciation genetics, but it is becoming increasingly clear that the model is too general to generate more specific predictions regarding the genetic mechanisms involved. Accumulating evidence indicates that the merging of two distinct genomes typically sets in motion extensive modifications of the genome and transcriptome, creating cascades of novel gene expression patterns (Michalak and Noor, 2003;Wu et al, 2003;Ranz et al, 2004;Auger et al, 2005;Hegarty et al, 2006), regulatory interactions and new phenotypic variation (Riddle and Birchler, 2003;Adams and Wendel, 2005a, b), chromosomal rearrangements (Rieseberg et al, 2003;Metcalfe et al, 2007), transposable element mobilization (Liu and Wendel, 2000;Shan et al, 2005;Ungerer et al, 2006), miRNA deficiency (Michalak and Malone, 2008) and DNA methylation changes (Waugh O'Neill et al, 1998;Vrana et al, 2000;Salmon et al 2005;Josefsson et al, 2006).…”
mentioning
confidence: 99%
“…The recent studies on a rice MITE (Jiang et al 2003;Kikuchi et al 2003) confirmed the cut-and-paste mechanism and indicated that amplification could be influenced by specific (environmental or genomic) conditions ( Jiang et al 2003;Shan et al 2005). However, although putative autonomous partners have been proposed for several MITE families, a clear demonstration that they are indeed necessary for MITE transposition is still lacking.…”
mentioning
confidence: 99%
“…In general terms, MITE-like elements have been widely described in plants ( Moreno-Vazquez et al, 2005 ;Lin et al, 2006 ;Guermonprez et al, 2008) and specifically in grapevine (Benjak et al, 2009), maize (Bureau & Wessler, 1992;Zerjal et al, 2009), cereal grasses (Bureau & Wessler, 1994), Arabidopsis (Feschotte & Mouches, 2000), rice (Feschotte et al, 2003 ;Jiang et al, 2003 ;Nakazaki et al, 2003 ;Shan et al, 2005), Medicago (Grzebelus et al, 2007(Grzebelus et al, , 2009, apple (Han & Korban, 2007), beet (Menzel et al, 2006), barley (Lyons et al, 2008;Petersen & Seberg, 2009), grasses (Park et al, 2003), pearl millet (Remigereau et al, 2006) and pome fruit trees (Wakasa et al, 2003). Descriptions in other organisms, such as bacteria (Chen et al, 2008), cyanobacteria , fungi (Xu et al, 2010), silkworms (Han et al, 2010), fish (de Boer et al, 2007) and amphibians (Hikosaka et al, 2011) are also found in the literature, but few occurrences have been reported in the Drosophila genus (Tudor et al, 1992 ;Miller et al, 2000 ;Ortiz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%